Analisis Pengaruh Faktor-Faktor Gamification dan Enjoyment Dalam ShopeeGames terhadap Online Purchase Intention pada Aplikasi Shopee - Eldhia, Abigail Mutiara; Iriyanti, Ira (Jurnal Manajemen dan Usahawan Indonesia, 2022)
The growth of technology has prompted changes in consumer shopping behavior to become more practical and e-commerce has become an option both globally and in Indonesia. This makes e-commerce, especially in Indonesia, compete to provide the best services and offers for consumers by continuing to innovate. One of the innovations made is to implement gamification. With gamification, the components used for the game design process are applied in the context of the non-game, which in this case is on e-commerce. The purpose of this study was to find out how the gamification dynamics can affect consumer enjoyment and further impact online purchase intention. The research design is conclusive descriptive with quantitative methods using a self-administered questionnaire. There were 254 respondents aged 18-55 years in Indonesia who are Shopee Games users in the last six months participating in the research. Data were analyzed using Partial Least Squares - Structural Equation Modeling (PLS-SEM) and processed with SPSS and SmartPLS. The results show that autonomy, rewards, and absorption have an influence on enjoyment which then affects online purchase intention.